Simulasi Perjalanan Harian Pegawai Unsyiah Untuk Efisiensi Waktu Keberangkatan Terbaik Berdasarkan Model Lalu Lintas Kendaraan - Elizar Elizar; Afdhal Afdhal (Universitas Syiah Kuala, 2015)
High traffic densitiy becomes one of a big problem of transportation in many big developing cities in Indonesia. The growth number of vehicles relatively much higher if compared to the growth of road infrastructure. Banda Aceh as a central city of Aceh Province are also facing moreless the same transportation problem,where traffic becomes very usual especially in peak hour in the morning when many people start their activity. It also happened in the afternoon when most of Banda Aceh people especially the one who work as a government servant going back from work. This research is trying to analyze one of the case of daily going to work travel route of Unsyiah administration staf. The result is very important to analyze the best departure time for the staff to minimize travel time. This research have developed a simulation model using an IT technology based on vehicle traffic mobility model. The simulation offered the fastest travel time solution with the best departure time to arrive at the destination by avoiding morning peak time traffic.